PENGARUH KEPUASAN KERJA, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KOMITMEN ORGANISASI DAN KINERJA DOSEN PADA UNIVERSITAS ROKANIA ROKAN HULU - Akmal, Junifar; Rangkuti, Taufik Indra (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This studylaims tolanalyze the influence of joblsatisfaction, leadership, and workldiscipline on organizational commitment and lecturer performance at Rokania University, Rokan Hulu. This research is a quantitativelstudy conducted by distributing G-Form questionnaires to respondents. The population in this study includes all lecturers at Rokania University, Rokan Hulu, totaling 34 individuals. The sampling method used is the census method, resulting in a total sample of 34 respondents. The data analysis techniques applied include descriptive statistical analysis, questionnaire feasibility testing, classical assumption testing, and multiple linear regression using SPSS software. The findings of this study reveal that job satisfaction and leadership partially have a positive but not significant effect on organizational commitment. Meanwhile, work discipline has a negative but not significant effect on organizational commitment. Job satisfaction has a positive and significant impact on lecturer performance, while leadership has a positive but not significant effect on lecturer performance. Additionally, work discipline and organizational commitment have a positive and significant influence on lecturer performance